2020
DOI: 10.1002/rcr2.518
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab as add‐on therapy in a patient with severe asthma and OSA

Abstract: Obstructive sleep apnoea (OSA) syndrome, the most frequent sleepdisordered breathing, is a comorbidity of asthma, whose prevalence covers about 49.5% of asthmatic adult patients. A 61-year-old female patient, affected by severe allergic asthma and obesity, started treatment with omalizumab and underwent polysomnography showing a severe OSA pattern (apnoea/hypopnoea index (AHI): 72.7). After six months, she showed functional improvement and good asthma symptoms control and underwent a new polygraphy for the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Another important finding is the marked improvement in nocturnal hypoxemia (a ~90% reduction in T 90 ) with almost complete resolution of gas exchange alterations during sleep. This improvement is also significant in view of the result of the study by Scioscia et al [6]. Indeed, a slight proportion of nocturnal hypoxemia persists after treatment with omalizumab (T 90 ~12%), whereas benralizumab appears to resolve the profile completely (T 90 ~2%).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Another important finding is the marked improvement in nocturnal hypoxemia (a ~90% reduction in T 90 ) with almost complete resolution of gas exchange alterations during sleep. This improvement is also significant in view of the result of the study by Scioscia et al [6]. Indeed, a slight proportion of nocturnal hypoxemia persists after treatment with omalizumab (T 90 ~12%), whereas benralizumab appears to resolve the profile completely (T 90 ~2%).…”
Section: Discussionmentioning
confidence: 76%
“…Another study evaluated the efficacy of omalizumab, a monoclonal antibody anti- IgE in the treatment of severe asthma, in a patient with an overlap syndrome of asthma and OSA. In that study the authors demonstrated that as asthma symptoms improved, polysomnographic indices also improved [ 6 ]. Similar to our case, a reduction in AHI was observed (~56%) even though OSA still persisted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case series of five patients with severe asthma with chronic rhinosinusitis, nasal polyposis, and OSA found a remarkable reduction in OSA symptoms in all patients after 6 months of therapy with dupilumab, an IL-4 and IL-13 antagonist [54]. Similarly, in another case, AHI halved after 6 months of asthma therapy with the anti-IgE antibody omalizumab [55].…”
Section: How Asthma Treatments Affect Osamentioning
confidence: 87%